Programmable Local Orientation of Micropores by Mold‐Assisted Ice Templating. Issue 2 (18th December 2020) - Zhou, Xiaohong; Yin, Liang; Yang, Baisong; Chen, Chuyang; Chen, Wenhui; Xie, Yu; Yang, Xichen; Pham, Jonathan T.; Liu, Sheng; Xue, Longjian
Abstract: Pore geometry plays a crucial role in determining the properties and functions of porous materials. Various methods have been developed to prepare porous materials that have randomly distributed or well‐aligned pores. However, a technique capable of fine regulation of local pore orientation is still highly desired but difficult to attain. A technique, termed mold‐assisted ice templating (MIT), is reported to control and program the local orientation of micropores. MIT employs a copper mold of a particular shape (for instance a circle, square, hexagon, or star) and a cold finger to regulate the 3D orientation of a local temperature gradient, which directs the growth of ice crystals; this approach results in the formation of finely regulated patterns of lamellar pore structures. Moreover, the lamellar thickness and spacing can be tuned by controlling the solution concentration. Abstract : A technique of mold‐assisted ice templating (MIT) is reported to fabricate programmable, local‐orientation‐controllable micropores. MIT employs a copper mold with designed shape and a cold finger to regulate the 3D orientation of the local temperature gradient, which directs the growth of ice crystals, resulting in the finely regulated patterns of lamellar pore structures.